PENGARUH MOTIVASI TERHADAP PRESTASI KERJA DI KANTOR CAMAT PONTIANAK UTARA KOTA PONTIANAK - Juetha E.42009020, Kristina Theresa (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This research point is to know and analyse the Motivation influence to achievement’s work of Pontianak Utara District office. Through statistical test of simple linear regression by using existing population amount by 24 people.The researcher submit hypotesis the motivation influence to achievement’s work are Hypotesis O (Ho): There are no effect motivation to achievement’s of Pontianak Utara  District office and Alternative Hypotesis (Ha): Motivation effect achievement’s work of Pontianak Utara District office.Result of research indicates that is correlation coefficient (R) equal to 0,797 and equation of regresi Y = 6,670 + 1,049 X. Pursuant to statistical analysis, indicators of this research have the characters of valid and reliable. Hypothesis result indicates that the test F obtained from Fcount equal to (38,239) > Ftable (4,30) with the probability values (sig) = 0,000 smaller than probability values 0,05, which is means Ha accepted and Ho refused. Researcher’s hypothesis proven to be that motivation effect to achievement’s work. Key Words : Motivation and achievement’s work